Tahlilan dalam Budaya Islam: Antara Tradisi Keagamaan dan Transformasi Sosial-Ekonomi - Rakhmi, Atik; Robiansyah, Firman; Rhamadani, Putri; Anisa, Siti (LP2M UIN Sunan Kalijaga, 2025)
Tahlilan is a tradition that has been embedded in the culture of the Indonesian Muslim community and is often considered an obligation in commemorating death. For some people, tahlilan is not only a religious activity, but also reflects the social dynamics of community interaction. In addition to its religious value, tahlilan tradition can also bring socio-economic impacts, especially for families who have financial limitations. The literature review research method was chosen in this study with the aim of analyzing the tahlilan tradition as an Islamic socio-cultural phenomenon that affects the lives of Indonesian people in religious, social and economic essence. By utilizing literature review, this research is able to explore the meaning of tahlilan in the religious traditions that develop in Indonesian society and examine the transformation of socio-economic pressures that affect tahlilan events. The results show that tahlilan can reflect the social dynamics of Indonesian society, but the socio-economic pressures that arise in holding tahlilan traditions often make sincerity in worship a little marginalized by a sense of obligation that is more cultural. However, with the advancement of economic lifestyles, in big cities tahlilan events have diminished. Although for some people, tahlilan has become an economic pressure due to the expense, it does not prevent them from carrying out this tradition.